Severe Toxicity in Nonhuman Primates and Piglets Following High-Dose Intravenous Administration of an Adeno-Associated Virus Vector Expressing Human SMN - Hinderer, Christian (Hum Gene Ther, 2018)
Neurotropic adeno-associated virus (AAV) serotypes such as AAV9 have been demonstrated to transduce spinal alpha motor neurons when administered intravenously (i.v.) at high doses. This observation led to the recent successful application of i.v. AAV9 delivery to treat infants with spinal muscular atrophy, an inherited deficiency of the survival of motor neuron (SMN) protein characterized by selective death of lower motor neurons. To evaluate the efficiency of motor neuron transduction with an AAV9 variant (AAVhu68) using this approach, three juvenile nonhuman primates (NHPs; aged 14 months) and three piglets (aged 7–30 days) were treated with an i.v. injection of an AAVhu68 vector carrying a human SMN transgene at a dose similar to that employed in the spinal muscular atrophy clinical trial. Administration of 2 × 10(14) genome copies per kilogram of body weight resulted in widespread transduction of spinal motor neurons in both species. However, severe toxicity occurred in both NHPs and piglets. All three NHPs exhibited marked transaminase elevations. In two NHPs, the transaminase elevations resolved without clinical sequelae, while one NHP developed acute liver failure and shock and was euthanized 4 days after vector injection. Degeneration of dorsal root ganglia sensory neurons was also observed, although NHPs exhibited no clinically apparent sensory deficits. There was no correlation between clinical findings and T-cell responses to the vector capsid or transgene product in NHPs. Piglets demonstrated no evidence of hepatic toxicity, but within 14 days of vector injection, all three animals exhibited proprioceptive deficits and ataxia, which profoundly impaired ambulation and necessitated euthanasia. These clinical findings correlated with more severe dorsal root ganglia sensory neuron lesions than those observed in NHPs. The liver and sensory neuron findings appear to be a direct consequence of AAV transduction independent of an immune response to the capsid or transgene product. The present results and those of another recent study utilizing a different AAV9 variant and transgene indicate that systemic and sensory neuron toxicity may be general properties of i.v. delivery of AAV vectors at high doses, irrespective of the capsid serotype or transgene. Preclinical and clinical studies involving high systemic doses of AAV vectors should include careful monitoring for similar toxicities.